PEDAGOGICAL CONDITIONS OF CREATIVE FORMATION PERSONALITIES OF THE FUTURE TEACHER - H.Ye. Gribenko (Academy of Cognitive and Natural Sciences, 2022)
The article describes objective and subjective conditions of student's creative personality development in teaching and educational process of higher pedagogical education.